+0  
 
0
109
2
avatar

Let $f(x) = 4x - 7$, $g(x) = (x + 1)^2$, and $s(x) = f(x) + g(x)$. What is $s(3)$?

 

----------

 

Let $f(x) = 2x^2 + 3x - 9,$ $g(x) = 5x + 11,$ and $h(x) = -3x^2 + 1.$ Find $f(x) - g(x) + h(x).$

 

----------

 

Let $f(x) = 3x + 2$ and $g(x) = x^2 - 5x - 1.$ Find $f(g(x)).$

 

thanks

 Jan 31, 2021
 #1
avatar+120287 
+1

First one

g(x) =  (x + 1)^2 =  x^2  + 2x + 1

f(x)  = 4x  - 7

f(x) + g(x)   =  x^2 + 6x   -   6  = s(x)

s(3)  =  (3)^2  + 6(3)  - 6    =   21

 

Second one

f(x)   -  g(x)     =  ( 2x^2 + 3x - 9)  - (  5x + 11) =  2x^2  - 2x  - 20

f(x) - g(x) + h(x)    =    (2x^2  - 2x  - 20)  +  ( -3x^2 + 1)  =  -x^2 -2x -19

 

Last one

 

f(g)   means  that   we are  putting   g  into  f....so we have

 

3 ( x^2 -5x   -1 )  +   2  =

 

3x^2 - 15x  - 3  + 2

 

3x^2  - 15x   - 1

 

 

cool cool cool

 Jan 31, 2021
 #2
avatar
0

Thank you :D

Guest Jan 31, 2021

12 Online Users

avatar
avatar
avatar